DESAIN DIDAKTIS MATEMATIS PADA MATERI OPERASI HITUNG CAMPURAN - Ahmad Ahmad; Kiki Riska Ayu Kurniawati; Habib Ratu Perwira Negara (Jurnal El-Hikam, 2023)
The purpose of the research was to find out the mathematical didactic design prepared by the teacher on mixed arithmetic operations material at tsanawiyah madrasah. Sources of data in this study were teachers and students. This type of research is a case study, namely research that describes a problem by taking in-depth data about the actual conditions in the field. The results of this study are that in conveying the material on mixed arithmetic operations the teacher has not linked the concepts being taught with everyday life. The teacher does not use media to complement the learning of mixed arithmetic operations specifically because there are several obstacles. Student mistakes in the learning process are conceptual errors, careless errors, and errors in understanding the questions. In order for the learning process to run well, the teacher must design learning from the planning stage to the end of the learning activity. Beginning with the teacher designing how to convey the concept of mixed arithmetic operations material so that it is easier for students to understand, how can the teacher find out students' understanding of mixed arithmetic operations material, the teacher's strategy in conveying material and learning methods to facilitate students' understanding.